"The influence of emotional intelligence the oral proficiency of english as a second language in the students of the last semester of the english teaching career at UDELAS" - González Alvarez, Yessy Yamileth (UDELAS, 2011)
This work focuses on the positive relationship between the emotional intelligence and the learning of english as a second language . The emotional intelligence plays a key role within the learning process and it must be considered as a critical factor because it reduces anxiety and inhibitions; and the most important, it enhances learners motivation and self-esteem.